Rail Mounted Gantry Crane Scheduling In Rail–Truck Transshipment Terminal. Issue 1 (2nd January 2016) - Wang, Li; Zhu, Xiaoning; Xie, Zhengyu
Abstract: Rail mounted gantry crane (RMGC) scheduling is vital to handling efficiency in rail-truck transshipment terminals. In this paper, we propose an optimization model for RMGC scheduling problem based on a dual cycle mode. A genetic algorithm is designed to obtain the optimization handling sequence. Computational experiments on a specific rail-truck transshipment terminal show that the proposed method is effective to solve RMGC scheduling problems in rail-truck transshipment terminals.